2018
DOI: 10.3892/or.2018.6672
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of selective exosomal microRNA expression profile derived from laryngeal squamous cell carcinoma detected by next generation sequencing

Abstract: Exosomes are nanometer-scale extracellular vesicles derived from almost all types of cells and key signaling mediators between cancer cells and their microenvironment. Certain microRNAs (miRNAs) are selected for exosome packing and exclusion from parental cells, while other miRNAs are selectively retained by cells, suggesting a biological role for these miRNAs in tumor malignant progression. In the present study, we isolated and characterized the exosomes derived from the laryngeal squamous cell carcinoma (LSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…Coincidentally, Yamada et al found that colorectal cancer cell‐derived microvesicles comprising microRNA‐1246 stimulate angiogenesis by stimulating Smad 1/5/8 signaling prompted by PML downregulation in endothelial cells . We established that miR‐1246 is extremely augmented in sEV acquired from LSCC cell lines in previous research; however, in‐depth research about its specific mechanism was absent …”
Section: Introductionmentioning
confidence: 72%
“…Coincidentally, Yamada et al found that colorectal cancer cell‐derived microvesicles comprising microRNA‐1246 stimulate angiogenesis by stimulating Smad 1/5/8 signaling prompted by PML downregulation in endothelial cells . We established that miR‐1246 is extremely augmented in sEV acquired from LSCC cell lines in previous research; however, in‐depth research about its specific mechanism was absent …”
Section: Introductionmentioning
confidence: 72%
“…Exosomes are extracellular vesicles (30-100 nm), that acts as cargo for mRNAs, miRNAs, DNA fragments, proteins as well as apoptotic bodies [7]. Expression pattern of exosomal-derived miRNAs differ greatly between cancer and normal control cells [8,9], thereby hinting at the role of exosomal miRNAs as potential biomarker for cancer diagnosis, including OSCC. Several pioneering studies highlight the crucial role of exosomes in facilitating tumor growth, angiogenesis, invasion, metastasis as well as in conferring chemoresistance [10,11].…”
Section: Research Papermentioning
confidence: 99%
“…The resulting exosome supernatant was then ltered (0.22 μm lter) to eliminate cellular debris, followed by centrifugal ultra ltration (Amicon® Ultra-15 100 KDa; Merck KGaA) to prevent potential contamination. Exosomes were isolated from the ultra ltered supernatant with Ribo™ Exosome Isolation Reagent (RiboBio Co., Ltd., Guangzhou, China), as previously described [13]. Brie y, the collected conditioned medium was mixed with Ribo™ Exosome Isolation Reagent (ratio 3:1), followed by an incubation at 4˚C overnight.…”
Section: Collection Of Culture Supernatant and Isolation Of Exosomesmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) TEM was used to identify the morphological characteristics of exosome pellets, as described previously [13]. About 20 μL of exosome-PBS solution was added to carbon-coated copper grids for 1 min and then the excess solution was removed by blotting with lter paper.…”
Section: Collection Of Culture Supernatant and Isolation Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation